A statistical evaluation of the potential genotoxic activity in the surface waters of the Golden Horn Estuary - Kocak, Emel; Yetilmezsoy, Kaan; Gonullu, M. Talha; Petek, Mustafa (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The potential genotoxic activity in the surface waters of the Golden Horn Estuary was statistically evaluated utilizing a combination of appropriate parametric and non-parametric tests. The genotoxic activities that were associated with the water samples were determined by the SOS chromotest microplate assay. This assay utilizes beta-galactosidase activity, alkaline phosphatase activity, and four different solvent controls, to generate reliable results when corrected induction factors (CIF) are used as quantitative measurements of genotoxic activity. The CIF values were obtained from a total of 384 different genotoxic experiments that were grouped into subsets according to the respective seasons and the selected sampling locations. A total of 160 subsets were statistically compared to assess any possible differences between the pairs of groups, with 95% confidence limits. The findings of this study clearly indicate that some seasonal variations exist in the CIF values at several sampling sites. However, no potentially hazardous impact to the aquatic environment was found in the estuarine system. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Golden Horn; Genotoxicity; SOS chromotest; Statistical analysis; Mann-Whitney U test; SOS-CHROMOTEST; POLLUTED ESTUARY; SEDIMENTS; QUALITY; INDUSTRIAL; INDUCTION; IMPACT; ASSAY; Environmental Sciences & Ecology; Marine & Freshwater Biology